The emergence of a global administrative space in environmental governance: Mapping the administrative embeddedness of international environmental secretariats. - Jörgens, H. (Transnational Governance in a Time of Turbulence, 2025)
The paper investigates whether the concept of an administrative space - until now mostly applied to the European Union - can be extended to global environmental governance. Drawing on the DFG-funded TRANSPACE project, we operationalize the Global Administrative Space through three empirically observable dimensions: institutional independence, inter-institutional integration, and co-optation. Using original survey data from 1,109 organizations and Social Network Analysis, we map the administrative networks surrounding the UNFCCC and CBD regimes, revealing patterns of cooperation and information exchange among international public administrations, state agencies, and non-state actors. To assess whether this administrative space influences policy outputs, we employ computational text analysis - including Named Entity Recognition and ClimateBERT - on 14 European Green Deal documents. Preliminary findings suggest that mentions of international organizations and agreements correlate with higher climate policy ambition, while co-mentions of member states and international bodies may attenuate individual positive effects. Our analysis indicates that Global Administrative Spaces can be theorized, operationalized, and empirically observed, and that they may exert autonomous influence on policy outputs beyond that of individual organizations.